In-situ additive manufacturing of high strength yet ductility titanium composites with gradient layered structure using N2 - Xiao, Yunmian; Song, Changhui; Liu, Zibin; Liu, Linqing; Zhou, Hanxiang; Wang, Di; Yang, Yongqiang (International Journal of Extreme Manufacturing, 2024)
It has always been challenging work to reconcile the contradiction between the strength and plasticity of titanium materials. Laser powder bed fusion (LPBF) is a convenient method to fabricate innovative composites including those inspired by gradient layered materials. In this work, we used LPBF to selectively prepare TiN/Ti gradient layered structure (GLSTi) composites by using different N2–Ar ratios during the LPBF process. We systematically investigated the mechanisms of in-situ synthesis TiN, high strength and ductility of GLSTi composites using microscopic analysis, TEM characterization, and tensile testing with digital image correlation. Besides, a digital correspondence was established between the N2 concentration and the volume fraction of LPBF in-situ synthesized TiN. Our results show that the GLSTi composites exhibit superior mechanical properties compared to pure titanium fabricated by LPBF under pure Ar. Specifically, the tensile strength of GLSTi was more than 1.5 times higher than that of LPBF-formed pure titanium, reaching up to 1100 MPa, while maintaining a high elongation at fracture of 17%. GLSTi breaks the bottleneck of high strength but low ductility exhibited by conventional nanoceramic particle-strengthened titanium matrix composites, and the hetero-deformation induced strengthening effect formed by the TiN/Ti layered structure explained its strength-plasticity balanced principle. The microhardness exhibits a jagged variation of the relatively low hardness of 245 HV0.2 for the pure titanium layer and a high hardness of 408 HV0.2 for the N2in-situ synthesis layer. Our study provides a new concept for the structure-performance digital customization of 3D-printed Ti-based composites.